(untitled) (Ukrainian Journal of Ophthalmology, 2025)
According to the literature, there are two equivalent terms "optic neuritis" and "inflammatory optic neuropathy". Classification, pathogenesis and clinical manifestations are ambiguous. However, the growing interest in the problems of demyelinating and infectious diseases contributes to detailing the data on the mechanisms of certain forms of optic nerve inflammation. Purpose. To study the current views on the pathogenesis of optic nerve inflammation. Methods. The literature search in Ukrainian and foreign scientific sources was performed. Modern diagnostic methods such as optical coherence tomography (OCT), magnetic resonance imaging (MRI), immunological and virological tests allow studying i) the role of factors, individual and in combinations, in the development of neuritis, ii) the changes in visual functions, iii) damage to individual structural elements of the visual system, and iv) recovery from the damage received. Conclusion. The analysis of literature data on optic neuritis and/or inflammatory optic neuropathy showed a high topical interest of the scientific community. Further studies are likely to improve the current classifications of optic nerve inflammation and develop a differentiated approach to the treatment of optic nerve inflammation.